Treatment of laparoscopic cholecystectomy complication of hemobilia by selective arterial embolization - Muharrem TOLA; Mehmet YURDAKUL; Turhan CUMHUR; Burhan ŞAHİN and Fatih HİLMİOĞLU (Turkish Journal of Gastroenterology, 2019)
-